Application of the Analytical Hierarchy Process (AHP) Method in Selecting Warehouse Locations for Onlineshop Goods Storage (Case Study: Expedited Shipment of Finished Goods): Pengaplikasian Metode Analytical Hierarchy Process (AHP) Dalam Pemilihan Lokasi Gudang Penyimpanan Barang Onlineshop (Studi Kasus : Expedisi Pengiriman Barang Jadi ) - dwi febryanto, Indra; berlianto, rahmat; prihono, prihono (Universitas Muhammadiyah Sidoarjo, 2022)
Storage of finished goods is one of the important factors needed by a company, both offline and online manufacturing. The problem that often occurs is the lack of area and inadequate warehouse locations for storing finished goods. This problem is also found in the activities of storing finished goods in shipping expeditions. The condition of the warehouse which was initially less efficient was due to the location of the warehouse being less spacious, the absence of safety equipment and also areas prone to flooding. The goal to be achieved is to choose the optimal warehouse location from several existing alternatives. The method used is the Analytical Hierarchy Process (AHP) method to develop a hierarchy of logistics center location selection. Research variables using criteria include distance, cost, facilities, geographical position and warehouse area. The results of data processing produce the highest criterion weight value of 0.3228, namely the area of ​​the warehouse and the smallest criterion weight of 0.0417, namely the cost criterion. In addition, the highest value of the work alternative is 0.4085 on the SPILL warehousing alternative and the smallest value is 0.2749 on the Rungkut Industri alternative.